DISTILLATION OF ESSENTIAL OILS FROM PATCHOULI LEAVES USING SOLAR ENERGY (PHOTOVOLTAIC) AS A HEATING SOURCE - Prayogi, Muhammad Akbar; Rihayat, Teuku; Zaini, Halim (Jurnal Sains dan Teknologi Reaksi, 2023)
Currently, the use of the sun as renewable energy is very effective. Solar Cells or commonly called Photovoltaic systems are components used to absorb heat from sunlight which is converted into electrical energy. This photovoltaic technology is very well implemented in Indonesia because of the tropical climate and long exposure to sunlight. Of the many types of essential oils, one of the most prominent in Indonesia is patchouli oil. Currently, essential oil refining still uses energy sources that can be scarce at any time and are less environmentally friendly. In this research, we tried to design a distillation device using solar cells to produce electricity which will later be used as a heating source. The highest yield obtained was 2.60% at a drying time of 32 hours and a distillation time of 420 minutes and the lowest yield obtained was 0.94% at a drying time of 0 hours and a distillation time of 300 minutes. From the results of analysis using GC-MS, it shows that the chemical compounds identified include 4,7-Methanoazulene, Seychellene, and several other compounds. Based on the GC-MS results, patchouli alcohol was 37.18% and 4,7-Methanoazulene was 2.78%. According to International Market Standards, the patcholi alcohol content must be higher than 30%, therefore this material meets the Indonesian National Standard (SNI).Keywords : Solar Cell, Patchouli Oil, Distillation Equipment, Indonesian National Standard